Multimodal Imaging in a Patient With Alzheimer Disease and Parkinsonism Because of a Presenilin-1 Mutation. (September 2021) - Lu, Jia-Ying; Sun, Yi-Min; Yen, Tzu-Chen; Zuo, Chuan-Tao; Wang, Jian
Abstract : Abstract: A correct clinical diagnosis of motor dysfunction accompanied by cognitive impairment remains challenging. Recent advances in molecular imaging biomarkers hold promise to overcome this issue. A 37-year-old woman presenting with parkinsonism and cognitive impairment underwent both multimodal neuroimaging and genetic testing. Her main findings on PET included diffuse tau accumulation in the cerebral cortex and left putamen, increased cerebellar amyloid deposits, asymmetrically reduced dopamine transporter binding, and mild hypermetabolism in the putamen. Genetic analysis revealed the presence of a presenilin-1 mutation (C.1157T>G). These findings suggested a diagnosis of early-onset autosomal dominant Alzheimer disease accompanied by parkinsonism.